ANALYSIS OF THE EFFICIENCY OF CAPITAL, LABOR, AND TECHNOLOGY UTILIZATION IN THE BONE CRAFT INDUSTRY IN TAMPAKSIRING VILLAGE - Pande Putu Selvi Ari; Amrita Nugraheni Saraswaty (Adisam Publisher, 2025)
The industrial sector plays a crucial and strategic role in regional economic development, offering substantial benefits for local economic advancement, including in the bone craft industry in Gianyar. This study aims to analyze the efficiency of capital, labor, and technology utilization in the bone craft industry in Tampaksiring Village. It employs a quantitative associative research design. The study was conducted in Tampaksiring Village, Tampaksiring District, Gianyar Regency. The population comprises all bone craft industries in the village, with a sample size of 57 business units determined using a saturated sampling technique. Data were collected through observation, structured interviews using questionnaires, and in-depth interviews. The data analysis techniques included multiple linear regression, F-test (simultaneous test), t-test (partial test), and production factor efficiency analysis. The results show that: (1) capital, labor, and technology simultaneously have a significant effect on the production of bone craft industries in Tampaksiring Village; (2) capital, labor, and technology each have a positive and significant effect on production; and (3) the efficiency values of capital, labor, and technology usage are < 1, indicating an inefficient condition.